2023
DOI: 10.1038/s41467-023-39135-8
|View full text |Cite
|
Sign up to set email alerts
|

In vivo PAR-CLIP (viP-CLIP) of liver TIAL1 unveils targets regulating cholesterol synthesis and secretion

Abstract: System-wide cross-linking and immunoprecipitation (CLIP) approaches have unveiled regulatory mechanisms of RNA-binding proteins (RBPs) mainly in cultured cells due to limitations in the cross-linking efficiency of tissues. Here, we describe viP-CLIP (in vivo PAR-CLIP), a method capable of identifying RBP targets in mammalian tissues, thereby facilitating the functional analysis of RBP-regulatory networks in vivo. We applied viP-CLIP to mouse livers and identified Insig2 and ApoB as prominent TIAL1 target trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…This review integrates the new insights from the recent literature with what had been learned previously into an extended, detailed working model of VLDL biogenesis and secretion (Figure 2). It has been well-established that VLDL is regulated at the posttranslational level (reviewed in the study by Ginsberg and Fisher 86 ), but we here list several studies that have provided evidence for additional regulation at the transcriptional level (HUR 13 ) and strong evidence for regulation at the translational level at the outer ER membrane (VIGILIN and TIAL1 14,15 ). In addition, LZP 19 and MDM2 20 can be added as members of a large number of proteins that were previously shown to affect apoB/VLDL at the early posttranslational level (Table ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This review integrates the new insights from the recent literature with what had been learned previously into an extended, detailed working model of VLDL biogenesis and secretion (Figure 2). It has been well-established that VLDL is regulated at the posttranslational level (reviewed in the study by Ginsberg and Fisher 86 ), but we here list several studies that have provided evidence for additional regulation at the transcriptional level (HUR 13 ) and strong evidence for regulation at the translational level at the outer ER membrane (VIGILIN and TIAL1 14,15 ). In addition, LZP 19 and MDM2 20 can be added as members of a large number of proteins that were previously shown to affect apoB/VLDL at the early posttranslational level (Table ).…”
Section: Discussionmentioning
confidence: 98%
“…The same investigators recently showed that TIAL1 (TIA1 cytotoxic granule-associated RNA-binding protein like 1) 14 -another RNA-binding protein-could affect VLDL metabolism. Loss of TIAL1 in mice markedly reduces apoB synthesis by 50% with a 31% reduction in VLDL secretion but increases in hepatic triglycerides and cholesterol.…”
Section: Transcription and Translationmentioning
confidence: 99%
See 2 more Smart Citations